Cartographie De La Sensibilite Aux Maladies Environnementales Respiratoires Dans Le District Sanitaire De Koumassi-Port-Bouët-Vridi (Sud De La Côte d’Ivoire) - Damien, Kouame Adonis Krou; Maïmouna, Fofana Kandana Eve; Hervé, Mobio Abaka Brice; Jean-Baptiste, Kassi Ahon; Fernand, Kouame Koffi; Valère, Djagoua Eric M’moi (European Scientific Journal, ESJ, 2017)
In Côte d’Ivoire morbidity causes are related to diseases such as malaria, diarrhea, and acute respiratory infections (ARI), which are constantly evolving. Koumasi and Port-Bouet are the most affected municipalities in the country. This study aims to find environmental determinants of spatial distribution of the ARIs and identify the most sensitive areas to take action for prevention and effective control and targeted in order to reduce the prevalence of ARI. To achieve this goal, we have identified environmental factors associated with the occurrence of ARI. Different environmental and cartographic data were integrated into a GIS. A multi-criteria analysis was performed to determine the environmental parameters that expose more people to the occurrence of the IRA and the weights of these parameters. The combination of exposure maps was used to map the sensitivity to IRA. Multi-criteria analysis revealed that refuse dumps have the highest influence in the occurrence of the disease, followed by industrial facilities and permanent wastewater. The ARI sensitivity map obtained shows that neighborhoods Nord-est 2 and Zone industrielle in Koumassi municipality are most susceptible to ARI. In the municipality of Port-Bouet sensitivity is more pronounced at Vridi canal and Vridi 3. Special attention should therefore be granted these neighborhoods.